PENJAMINAN MUTU (QUALITY ASSURANCE) DAN INTERNATIONAL ORGANIZATION FOR STANDARDIZATION (ISO) PADA PERGURUAN TINGGI - Ariati Anomsari (JURNAL DIAN, 2011)
University is an institution which has a function and competency in running and expanding the process of higher education, analyzing and developing the science and technology then those will be applied for the society and environmental sustainabitity. Quality Assurance is the controlling structure in delivering higher education based on law and national education system which applies the horizontal controlling done by university, stakeholders, and government. The government determines the national policy and standard. Quality assurance is a system of management which needs standard management system. ISO-9000 is a standard of quatity assurance which has been applied by most organizations. By using ISO-9000, a university will obtain good quality assurance and international standard.Keyword : Science and technology, national education system, stakehotders, Quality Assurance, ISO